Characteristics Of Intellectual Development In Adolescents - Sayfullayeva Zuhra Izzatillayevna (Genius Publishing Group, 2023)
The task of establishing the level of intelligence has been one of the most important in psychology since the formation of this science. It was the intellectual indicator of a person that made it possible to characterize his mental and moral qualities.
Keywords: Adolescent; reading activity; intellectual development; attention